Visualizing Association of the Retroviral Gag Protein with Unspliced Viral RNA in the Nucleus - Rebecca J. Kaddis Maldonado (American Society for Microbiology, 2020)
ABSTRACT Packaging of genomic RNA (gRNA) by retroviruses is essential for infectivity, yet the subcellular site of the initial interaction between the Gag polyprotein and gRNA remains poorly defined. Because retroviral particles are released from the plasma membrane, it was previously thought that Gag proteins initially bound to gRNA in the cytoplasm or at the plasma membrane. However, the Gag protein of the avian retrovirus Rous sarcoma virus (RSV) undergoes active nuclear trafficking, which is required for efficient gRNA encapsidation (L. Z. Scheifele, R. A. Garbitt, J. D. Rhoads, and L. J. Parent, Proc Natl Acad Sci U S A 99:3944–3949, 2002, https://doi.org/10.1073/pnas.062652199; R. Garbitt-Hirst, S. P. Kenney, and L. J. Parent, J Virol 83:6790–6797, 2009, https://doi.org/10.1128/JVI.00101-09). These results raise the intriguing possibility that the primary contact between Gag and gRNA might occur in the nucleus. To examine this possibility, we created a RSV proviral construct that includes 24 tandem repeats of MS2 RNA stem-loops, making it possible to track RSV viral RNA (vRNA) in live cells in which a fluorophore-conjugated MS2 coat protein is coexpressed. Using confocal microscopy, we observed that both wild-type Gag and a nuclear export mutant (Gag.L219A) colocalized with vRNA in the nucleus. In live-cell time-lapse images, the wild-type Gag protein trafficked together with vRNA as a single ribonucleoprotein (RNP) complex in the nucleoplasm near the nuclear periphery, appearing to traverse the nuclear envelope into the cytoplasm. Furthermore, biophysical imaging methods suggest that Gag and the unspliced vRNA physically interact in the nucleus. Taken together, these data suggest that RSV Gag binds unspliced vRNA to export it from the nucleus, possibly for packaging into virions as the viral genome. IMPORTANCE Retroviruses cause severe diseases in animals and humans, including cancer and acquired immunodeficiency syndromes. To propagate infection, retroviruses assemble new virus particles that contain viral proteins and unspliced vRNA to use as gRNA. Despite the critical requirement for gRNA packaging, the molecular mechanisms governing the identification and selection of gRNA by the Gag protein remain poorly understood. In this report, we demonstrate that the Rous sarcoma virus (RSV) Gag protein colocalizes with unspliced vRNA in the nucleus in the interchromatin space. Using live-cell confocal imaging, RSV Gag and unspliced vRNA were observed to move together from inside the nucleus across the nuclear envelope, suggesting that the Gag-gRNA complex initially forms in the nucleus and undergoes nuclear export into the cytoplasm as a viral ribonucleoprotein (vRNP) complex.